An Experimentally Verified LC‐MS Protocol toward an Economical, Reliable, and Quantitative Isotopic Analysis in Nitrogen Reduction Reactions. Issue 5 (18th March 2021) - Saji, Sandra Elizabeth; Lu, Haijiao; Lu, Ziyang; Carroll, Adam; Yin, Zongyou
Abstract: To substitute the energy‐intensive Haber‐Bosch process for the synthesis of ammonia, some labile techniques, such as photocatalysis, electrocatalysis, photoelectrocatalysis, and photothermocatalysis, have emerged and attracted intense research interest. However, the contamination of the reaction system is one of the major concerns on how to reliably and accurately evaluate the performance of these catalysts, which is why various control studies are involved. Isotopic labeling studies are one of the most reliable control strategies in nitrogen fixation experiments, to ensure that N2 is exclusively the source of the generated ammonia. As a convenient, sensitive and accurate technique distinguished with a quantitative atomic mass resolution, liquid chromatography‐mass spectrometry (LC‐MS) has been extensively employed for the detection of ammonia in aqueous electrolyte systems. However, the previous work protocols for 15 N2 isotopic analysis using LC‐MS either involved hazardous procedures which could potentially damage the instrument, or lacked in their experimental verification using real samples. Herein, a safe, reproducible and economical protocol for the detection of ammonia using LC‐MS is presented, exhibiting an exponentially steep progressive detectivity of 15 N abundance, well verified with a series of experimental results for nitrogen reduction reactions. This is expected to provide a prudent cost‐effective and sustainable gateway into isotopic analysis. Abstract : A safe, reproducible, and economical protocol for the detection of isotopic ammonia using LC‐MS is presented, exhibiting an exponentially steep progressive detectivity of 15 N abundance, which is well verified with a series of experimental results for nitrogen reduction reactions. This study provides a prudent, cost‐effective, and sustainable gateway into isotopic analysis.